Computed permeability for cement paste subject to freeze-thaw cycles at early ages. (30th May 2020) - Wei, Ya; Guo, Weiqiang; Wu, Zehong; Gao, Xiang
Highlights: The pore parameters are measured from MIP, BSE, and X-ray CT scanning techniques. The pore characteristics of cement pastes subject to freeze-thaw cycles are assessed. The intrinsic permeability of cement paste is obtained by three different methods. The GEM method is a more suitable tool for cementitious materials with low porosity. Abstract: Assessing the permeability of concrete subject to unexpected freeze-thaw cycles at early age is critical to ensure the durability and service life of concrete structures. However, measuring permeability of concrete and cement paste has been a challenge. In this study, the intrinsic permeability of cement paste is calculated by using Katz-Thompson equation, general effective media (GEM) method, and Navier-Stokes method based on the pore parameters measured from the mercury intrusion porosimetry (MIP), the backscattered electron (BSE) imaging, and the X-ray computed tomography (CT) techniques. The pastes are subject to freeze-thaw cycles at the age of 1 and 7 days followed by sealed curing until the age of 40 days. The water-to-cement ( w/c ) ratios of paste are 0.3 and 0.5, representing the high- and low-strength concrete, respectively. The measured pore characteristics and the calculated intrinsic permeability are then compared to that of the control samples. The measurable pore size range of each technique is quantified, and the applicability of each computing method for permeability is discussed. The results of this study provide the insight into the feasibility of different measuring techniques for pore parameters and the predicting methods for permeability, particularly for cementitious materials subject to freeze-thaw cycles.